Pengaruh Pengelolaan Akuntansi Pertanggungjawaban dan Strategi Perusahaan terhadap Efektivitas Kinerja - Airlangga Kaivalya; Vandu Mesa Nopandri (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to examine the effect of responsibility accounting management and corporate strategy on the effectiveness of organizational performance. Responsibility accounting plays an important role in compiling accurate and detailed financial information that allows companies to evaluate the performance of specific departments and business units. On the other hand, an effective corporate strategy serves as a guide in achieving long-term goals and value creation. In this context, this study integrates these two aspects to evaluate their impact on overall company performance. Using data from different industries and companies, this study applies quantitative analysis to measure the relationship between responsibility accounting management, strategy implementation, and key performance indicators such as profitability, operational efficiency, and company growth. The results show that effective integration between responsibility accounting and corporate strategy significantly affects the improvement of performance effectiveness. The findings offer practical insights for managers and business practitioners on how to optimize the use of responsibility accounting and strategy to achieve better performance goals.